Fruit and Vegetables Carotenoids Intake in Eight Latin American Countries, Results from the ELANS Study - Gómez Salas, Georgina (2020)
Objectives: To determine carotenoid intake (Beta and alpha carotene, lycopene and beta cryptoxanthin) from fruit and vegetable sources in ELANS participating countries. Methods: Data were obtained from the Latin American Health and Nutrition Study (ELANS), a multicenter study developed in urban areas of 8 Latin American countries: Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru and Venezuela. Dietary intake among 9218 participants (15- 65 y) was assessed using two 24-hour recall and processed by Nutritional Data System for Research (NDS-R).Fruits and vegetables were classified according to the 2002–2007 FAO Supply Utilization Accounts Data. Major food sources of carotenoids were assessed using weighed-proportions. Median intake, expressed as micrograms per day (mcg/d), and sources of carotenoids were performed by country. Results: ∗All data is presented as mcg/d The highest intake for betacarotene was reported in Ecuador (2659.6 ± 82.8) and the lowest in Brazil (1368.9 ± 42.2). The same trend was observed for alpha-carotene (290.6 ± 15.2 in Brazil vs 975.6 ± 33.5 in Ecuador). The main sources of these carotenoids are root vegetables such as carrots and beets. In the case of lycopene, Ecuador showed the highest average intake (3038.5 ± 174.3) whereas Peru showed the lowest (1111.7 ± 75.2). The most important source of this carotenoid is fruity vegetables, such as tomatoes. For beta cryptoxanthin, the highest intake was observed in Venezuela (246.3 ± 10.7) and the lowest was reported in Brazil (99.5 ± 5.3) Conclusions: Fruits and vegetables are important sources of carotenoids in the human diet. Of all countries included in this study, Brazil had the lowest intake of beta and alpha carotene and beta cryptoxanthin, and Ecuador had the highest intake of beta and alpha carotene and lycopene. Further studies are needed to assess bioavailability and serum concentrations in order to establish dietary recommendations regarding both pro vitamin and non pro-vitamin A carotenoids